Technological and Scientific Hebrew Terminology - Irmay, Ron (Meta, 1998)
AbstractThe author describes the procedures and mechanisms used by Israel's Central Committee for Technological Terminology (CCTT), a branch of the Academy of the Hebrew Language at Technion - Israel Institute of Technology, in the development and maintenance of standard Hebrew terminology in science and technology. Lexicographic and sociolinguistic processes involved in the formation of new scientific terms in Hebrew, such as the effect of synonyms, transliteration, international terms and linguistic structure, fuzzy usage, pressure of countries of origin, etc., are referred to along with a broad survey of the Central Committee's printed and computerized output over the years. In order to provide an updated terminological service that is easily accessible to the public, CCTT's Office at Technion is developing a computerized dictionary database for local and net-based multiuser environments.